Assimilation Undercuts Authenticity: A Consequence of Women's Masculine Self-Presentation in Masculine Contexts. (December 2020) - Dormanen, Rose; Sanders, Courtney S.; Maffly-Kipp, Joseph; Smith, Jessi L.; Vess, Matthew
We tested whether women's sense of authenticity can be compromised by the expression of masculine characteristics and whether feelings of authenticity directly or indirectly connect masculine expression to a diminished sense of interest in a science position. In Study 1 ( N = 105), we randomly assigned female undergraduates to present themselves as possessing traditionally high masculine characteristics or possessing non-masculine characteristics. They recorded a video "interview" for a science laboratory position and reported on their feelings of authenticity. Women in the masculine-expression condition reported less authenticity, which was in turn associated with less interest in the position. Study 2 ( N = 240 women) showed that expressing masculine characteristics in a written "application" led to lower levels of authenticity and, in turn, less interest in the position. This effect occurred most strongly among women relatively high in feminine identification and low in masculine identification. These studies indicate that women who express masculine characteristics in science settings may experience less authenticity, which can in turn contribute to diminished interest in a science position. These findings suggest that efforts to improve women's experiences in stereotypically masculine settings should focus on mitigating psychological connections between gender and success in those settings. Online slides for instructors who want to use this article for teaching are available on PWQ 's website athttp://journals.sagepub.com/doi/suppl/10.1177/0361684320947648